Participatory approaches enhance a sense of urgency and collective efficacy about climate change: Qualitative evidence from the world climate simulation. Issue 2 (3rd April 2023) - Hensel, Margaret; Bryan, Jovan; McCarthy, Carolyn; McNeal, Karen S.; Norfles, Nicole; Rath, Kenneth; Rooney-Varga, Juliette N.
Abstract: Despite clear scientific evidence to support an urgent need to cut greenhouse gas emissions, societal action remains inadequate to meet international climate goals. New approaches in climate change communication are needed to motivate climate action. World Climate is an interactive, engaging, and socially rich role-play simulation that challenges participants to negotiate a climate agreement to limit warming to 2 °C above pre-industrial levels. During the simulation, participants use a computer model, C-ROADS, to test their greenhouse gas emissions decisions and get immediate feedback on the resulting expected climate outcomes. In 2019, several programs that assist high school and college students who come from disadvantaged backgrounds implemented the World Climate simulation. In total, 39 participants who displayed the largest gains in their sense of urgency about climate change, measured through pre- and post-simulation surveys, were invited to participate in a semi-structured interview regarding their experience. Twelve individuals from four different simulation sessions were interviewed, and their responses were transcribed and categorized into codes. Results from this study show that interviewees attributed gains in their climate change risk perception to the simulation and also experienced gains in collective efficacy as a result. We constructed a causal loop diagram to visualize relationships between aspects of the simulation and gains in climate change beliefs, attitudes, and behaviors based on interview data. Insights from this qualitative study show that group deliberation guided by interaction with a model are important components to increasing urgency and climate action for the subset of the population interviewed.